2011
DOI: 10.1007/s13224-011-0044-5
|View full text |Cite
|
Sign up to set email alerts
|

Vibroacoustic stimulation and modified fetal biophysical profile for early intrapartum fetal assessment

Abstract: Objectives: To evaluate the efficacy of vibroacoustic stimulation (VAS) and modified fetal biophysical profile (mFBP) for early intrapartum fetal assessment and prediction of adverse perinatal outcome. Methods: In this prospective study, 210 women who were in latent phase of labor at the time of admission to the labor unit were subjected to VAS/mFBP, in which fetal startle response and fetal heart acceleration under combined B/M mode ultrasonography following VAS were observed. The results of VAS/mFBP were cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(20 citation statements)
references
References 15 publications
2
18
0
Order By: Relevance
“…In our RCT, we found insignificant differences between control and study groups in respect to perinatal outcome. Our observation is concordant with earlier studies 12 Contribution to authorship: SD and NJ conceived the idea. SD, BMR, PKS collected the data and followed up cases.…”
Section: Effect Of Vas On Perinatal Outcomesupporting
confidence: 92%
“…In our RCT, we found insignificant differences between control and study groups in respect to perinatal outcome. Our observation is concordant with earlier studies 12 Contribution to authorship: SD and NJ conceived the idea. SD, BMR, PKS collected the data and followed up cases.…”
Section: Effect Of Vas On Perinatal Outcomesupporting
confidence: 92%
“…Sood atul Kumar et al also reported comparable results in terms of perinatal deaths with sensitivity 100%, specificity 96.2%, positive predictive value 20%, negative predictive value 100%, and accuracy 96.2%. 1 VAST has increased in use over recent years as various researchers have found it comparable, cheaper, faster and less invasive than other tests of fetal well-being.…”
Section: Resultsmentioning
confidence: 99%
“…Intrapartum fetal assessment is aimed at identifying the fetus, that may be either already compromised in early labour or at an increased risk of compromise during late labour. 1 An early identification of such foetuses may help in instituting close surveillance to reduce perinatal morbidity and mortality. This may also help in utilising the available resource optimally in resource-constraint setting.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The findings of another research showed that vibroacoustic stimulation led to an increase in the fetal heart rate, reactivity, and heart rate accelerations (17,18).…”
Section: Discussionmentioning
confidence: 99%